An exploratory fMRI study on the association of parental involvement in childcare with brain responses to infant vocalisations and dyadic interaction quality in same-sex mother families - Paola Rigo (BMC Psychology, 2025)
Abstract It is of the utmost importance that children receive an appropriate adult response in order to ensure optimal child development. Prior research on parental brain networks has demonstrated that maternal brain activation in response to infant vocalisations exhibits a positive correlation with observed maternal sensitivity. However, the neurobiological foundations of responsiveness to child cues in mothers of same-sex families remain unexplored. Such an investigation could contribute to the expansion of the existing knowledge base regarding parental brain responsiveness and its relationship with factors associated with sensitive parenting, such as caregiving involvement. Twenty-one same-sex mothers were subjected to an fMRI listening task comprising positive and negative infant vocalisations. The degree of maternal involvement in the care of one’s own child and the quality of parent-child dyadic interactions (measured by the Emotional Availability (EA) Scales) were assessed. The results indicated a positive correlation between the degree of maternal involvement in childcare and maternal sensitivity and non-intrusiveness. Furthermore, mothers who demonstrated high levels of EA structuring and non-hostility during dyadic interactions exhibited increased activation in the right midbrain, temporal pole, extended to the insular cortex, in response to infant negative vocalisations. Finally, a consistent positive correlation was observed between the activation of the putamen in response to positive infant vocalisations and both the degree of maternal involvement in childcare and most of the maternal EA scales. Overall, preliminary findings in same-sex mothers suggest that optimal mother-child emotional connection is associated with time spent with and for the child in daily activities and with maternal brain responses to infant sounds in regions underlying emotion regulation, motivation and salience processing.